CDERA: Mapping hazards in the Caribbean - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2004)
Terry Ally reports on how the Caribbean Disaster Emergency Response Agency (CDERA) is compiling a catalogue of digital hazard maps that will enable farmers to assess flood risks.